Central Buton Regent Circular No. 01/54/2023 on the Proudly Made in Indonesia Movement in Goods and Services Procurement to Empower Local SMEs - Fajrin Tonny; Rizki Mustika S (Jurnal Hukum Volkgeist, 2024)
In implementing public services, the Government is expected to be able to provide maximum benefits for the welfare of the community. One of the objects that needs to be regulated is government policy in the field of procurement of goods and services. The regional government of Central Buton Regency has made efforts to increase the empowerment of micro business actors and small business actors and cooperatives as one of the policies ordered by Presidential Regulation Number 12 of 2021 concerning amendments to Presidential Regulation Number 16 of 2018 concerning Procurement of Government Goods/Services . Central Buton district government policy also encourages the use of Marketplaces and Electronic Catalogs, including national catalogs, sectoral catalogs and local catalogs. In writing, the regional government of Central Buton Regency issued several policies which are contained in regulations through Circular Letter number 54/01/2023 concerning the National Movement Proudly Made in Indonesia in the Procurement of Goods and Services within the Government of Central Buton Regency.